A new rust species of Diaphanopellis on Rhododendron oreodoxa from Southern China - Cao, Jing; Tian, Cheng Ming; Liang, Yingmei; You, Chong-Juan (Phytotaxa, 2017)
A novel rust species Diaphanopellis purpurea on Rhododendron oreodoxa collected in Southern China was identified and described. Light and scanning electron microscopy observations indicated that this rust species was morphologically distinct from other known Diaphanopellis species and Chrysomyxa species in teliospore morphology and urediniospore surface structure. Diaphanopellis purpurea can be phylogenetically separated from other Chrysomyxa species based on analysis of internal transcribed spacer (ITS) partial gene sequences. The aecial stage of the new species was also confirmed.